2005
DOI: 10.1038/sj.cdd.4401658
|View full text |Cite
|
Sign up to set email alerts
|

Integrins as a distinct subtype of dependence receptors

Abstract: In the absence of their cognate ligand, dependence receptors trigger programmed cell death. This function is the defining feature of dependence receptors, which include members of several different protein families. The integrins are a family of heterodimeric receptors for extracellular matrix (ECM) proteins, mediating cell anchorage and migration. Integrins share characteristics with dependence receptors, and integrin binding to substrate ECM ligands is essential for cell survival. Although integrins do not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 114 publications
4
51
0
1
Order By: Relevance
“…This controversy is further supported by the genetic identification in Drosophila melanogaster of an ALK ligand, jelly belly (jeb), which has no similarities with pleiotrophin or midkine Loren et al, 2003). Finally, in the particular case of integrins, the ligand must be an immobilized substrate ligand to block apoptosis as, contrary to other DRs, soluble ligand is not sufficient to counteract cell death induction (Stupack, 2005).…”
Section: Role Of Ligand Bindingmentioning
confidence: 99%
“…This controversy is further supported by the genetic identification in Drosophila melanogaster of an ALK ligand, jelly belly (jeb), which has no similarities with pleiotrophin or midkine Loren et al, 2003). Finally, in the particular case of integrins, the ligand must be an immobilized substrate ligand to block apoptosis as, contrary to other DRs, soluble ligand is not sufficient to counteract cell death induction (Stupack, 2005).…”
Section: Role Of Ligand Bindingmentioning
confidence: 99%
“…7 We will end this special issue with a review by Dwayne Stupack, who will describe a recently identified set of dependence receptors, integrins. 8 As usual, the reading of these reviews will raise more questions than they actually answer. What is the relation between integrins and DCC, molecules that do not display much sequence similarity?…”
mentioning
confidence: 99%
“…• mechanotransduction -a process of converting mechanical stimuli such as press or stretching to intracellular signals resulting in a specific gene expression, • regulation of vasomotor response: contraction (integrins α1β1 and α5β1) and relaxation (integrin αvβ3) of the vessel [15], • regulation of vessel permeability by modification of cadherins in endothelial adherent junctions and by contraction of collagen fibers in ECM (integrin α2β1) [20], • regulation of VSMCs tensegrity (resting tension in VSMC triggered by external mechanical forces, which influences myocyte behavior) [17], • activation of the cell death program [24]; integrins belong to a group of dependence receptors which lack of activity can lead to cell apoptosis, • modulation of cells shape by linkage with cytoskeletal actin and reorganization of actin filaments. In VSMCs, there are 13 combinations of integrins: α1β1, α2β1, α3β1, α4β1, α5β1, α6β1, α7β1, α8β1, α8β1, αVβ1, αVβ3, αVβ5, α6β4 [15,16].…”
Section: Introductionmentioning
confidence: 99%